THE“LAWS” OF RAPID SUCCESSFUL POSTCOMMUNIST TRANSFORMATIONAND ITS FAILURE: MULTI-VALUEQUALITATIVECOMPARATIVEANALYSIS - Norkus, Zenonas (Politologija, 2015)
The paper advances the deductive typology of the pathways of postcommunist transformation and their comparative qualitative analysis (QCA), using TOSMANAsoftware. The typology is constructed using three politomic (4 values) variables to describe the causal conditions of postcommunist transformation. These variables are orientation of postcommunist transformation, economic mode of the exit from Communism, and political mode of the exit from Communism. First variable describes the state of the economic and political culture of a communist country on the eve of the postcommunist transformation. Its values are continuation, restoration, imitation and innovation as kinds of cultural orientations. The values of the variable “economic mode of the exit from communism” are minimal, partial, gradual incremental and radical (shock therapeutic) market reforms. These 4 values are introduced to supersede the entrenched dichotomy of the gradualism and shock therapy. This dichotomy involves false identification of gradual and partial market reforms. The “partiality” means both incompleteness and non-impartiality of the market refoms. Gradual reforms can be complete if consequent, and they do not have redistributive consequences characteristic for partial reforms. Partial reforms lead to the redistribution enriching small minority at the cost of large majority. Shock therapy makes the majority of population the winners, but large minority is impoverished and excluded. This minority is small in the case of gradual incremental reforms. In most successful cases of such reforms (China and Vietnam), the exit from communism is Pareto optimal – there are no losers. Under minimal reforms, there are few loosers, but also only few winners. The values of the variable „political mode of the exit from Communism“ are conservation of the authoritarian regime, democratization from above, democratic revolution from below and “refolution” (pact of the excommunist and opposition elites). To describe the outcomes of postcommunist transformation, the dichotomic variables rational entrepreneurial capitalism, liberal democracy, liberal democratic capitalism (rational entrepreneurial capitalism + liberal democracy), political oligarchic capitalism, state capitalism are used. Because of the space limits, the multi-value QCA(mvQCA) is performed only for the outcome „liberal democratic capitalism“ after the first decade of postcommunist transformation. Due to this time limit, the regularities derived by mvQCAare qualified as those of „rapid“ transformation. For this analysis, the data set including 29 cases is used. They are are instances of the 17 from the 64 pathways how communism can be transformed into liberal democratic capitalism. To assign the values to cases for the variable “economic mode of the exit from Communism”, the thresholds derived from the EBRD annual “Transition Reports” were used. To assign the values for the variable “political mode of the exit from Communism”, the data and thresholds from the data set Polity IV (Polity IV Individual Country Regime Trends, 1946–2008) were used. The victory of communists or excommunists at the first free election was used as criterion to atribute the continuative orientation. The “laws” of postcommunist transformation are minimal Boolean formulas derived by TOSMANAallowing to make counterfactul assumptions about combinatorially possible, but empirically not available cases. To check these assumptions, a procedure for disciplined counterfactual analysis was applied. This procedure involves measuring Boolean distances between the empirically observed and non-observed configurations to find most similar cases for each non-observed configuration that was assumed by TOSMANAin the derivation of minimal formula. Using all available knowledge about the observed cases, most plausible answers about their most similar “what if...?” alternatives are estimated by qualitative judgment. After identifying most plausible outcome for each non-observed configuration, the data set was supplemented with 37 fictional cases, with total number of cases increasing up to 66, instancing 54 out of total 64 configurations of conditions. Two minimal formulas (one for positive and another for negative cases) were derived applying mvQCAto these sets, classified as ceteris paribus laws of the transformation of the communism into liberal democratic capitalism. Measuring these generalizations by some standard criteria of the lawlikeness, they qualify as laws, although final judgment may be postponed untill the construction of the complete theory of the postcommunist transformation using the procedure of the disciplined counterfactual speculation developed and applied in this paper for the first time in the research literature making use of the QCAtechniques.